ORGANISATIONAL CLIMATE AND EMPLOYEE ENGAGEMENT IN THE OIL AND GAS INDUSTRY - B. M. Nwibere (Journal Park Publishing, 2022)
This study investigated the relationship between organizational climate and employee engagement within the oil and gas industry using a cross-sectional survey research design. Simple random sampling was employed to select oil and gas companies, ensuring equal representation across the population. The Taro Yamen sampling technique determined a sample size of 129 respondents, allowing for comprehensive insights. Data collection utilized a closed-ended questionnaire structured on a five-point Likert scale, covering organizational climate, employee engagement, and demographic information. Descriptive statistics and multiple regression analysis were employed to analyze the data. The findings indicated a significant that leadership, work environment and organisational image had significant effect on employee enegagement, while trust and communication did not. These findings offer valuable insights for organizations in the oil and gas industry, highlighting the importance of fostering positive organizational climates to enhance employee engagement and ultimately improve organizational performance.
Keywords: Trust. Leadership. Communication. Work Environment. Organisational Image. Employee Engagement.